MODERN UNDERSTANDING OF MONEY AS AN ECONOMIC TOOL: THEORIES, FEATURES OF REGULATION, THE IMPACT OF SCIENTIFIC AND TECHNOLOGICAL PROGRESS - Butorov, Sergey; Apatova, Nataliya; Gerasimova, Svetlana; Zharova, Amina; Bugaeva, Tatyana; Reus, Semyon (Revista Inclusiones, 2020)
This article examines the role, meaning, and functions of money in the modern economy. The role of money as an economic category and an economic instrument influencing the economic development of the entire financial system and economic security and the search for ways to ensure sustainable innovative development are increasing under the influence of globalization processes and scientific and technological progress. The purpose of the research is to study money as an economic category that affects economic development through the tools of theory. The paper analyzes the norms of current legislation, statistical data, and the opinions of scholars on this issue. The article presents a comparative analysis of the regulation of various types of modern money, based on which it is concluded that there is no uniform approach to regulation, which slows down the involvement of advanced financial technologies in the world and domestic economic turnover. Proposals for improving the legal regulation of cryptocurrencies and electronic money have been presented.